Reinterpreting the Indonesia’s Relations with the Middle East towards the Era of Society 5.0 - Istadiyantha, Istadiyantha (Universitas Ahmad Dahlan, 2021)
This paper aimed at opening up opportunities to look for new meanings in Indonesia's relations with Middle Eastern countries, which are no longer a binary opposition, such as good and black and white, but are searching for colors and other positive meanings. Many people interpret an entity solely on the basis of a frozen meaning, a static meaning, and seem monotonous. Deconstruction seeks to offer a new meaning through re-actualization, redefinition, and/or re-interpretation. In general, this paper discusses the